Double-blind comparative study of two dosage regimens of cefaclor and amoxicillin-clavulanic acid in the outpatient treatment of soft tissue infections. - Pien, F D (1983)
A total of 88 patients were enrolled in a double-blind comparison of cefaclor and amoxicillin-clavulanic acid for the outpatient treatment of soft tissue infections (abscesses, cellulitis, and impetigo). In 84 clinically evaluable patients, high cure rates were obtained for all treatment groups (64 to 85%). Patients who received amoxicillin-clavulanic acid had a much higher incidence of gastrointestinal side effects than did patients who received cefaclor (34 versus 3%, P less than 0.005). However, only five patients with gastrointestinal reactions to amoxicillin-clavulanic acid had symptoms severe enough to warrant halting the completion of antibiotic therapy.